On why the gender employment gap in Britain has stalled since the early 1990s. Issue 6 (21st September 2020) - Razzu, Giovanni; Singleton, Carl; Mitchell, Mark
Abstract: Using over four decades of British micro data, this article looks at how the narrowing gender employment gap stalled in the early 1990s. Changes to the structure of employment between and within industry sectors impacted the gap at approximately constant rates throughout the period and do not account for the stall. Instead, changes to how women's likelihood of paid work was affected by their partners' characteristics explain most of the gap's shift in trend. Increases in women's employment when they had children or achieved higher qualifications continued to narrow the gap even after it had stalled overall.